Treatment of Mixed Azo Dyes in an Aerobic Sequential Batch Reactor and Toxicity Assessment Using Vigna radiata. (30th July 2022) - Akshaya Vidhya, T.; Veena Gayathri, K.; Senthil kumar, P.; Rangasamy, Gayathri; Kathawala, Tasneem M.
Abstract : Azo dyes are the most widely used dyes in the textile industry due to their stability, but their redundancy to degradation is of significant concern, particularly to aquatic ecosystems. In the present study, a lab-scale aerobic sequential batch reactor (SBR) was operated to analyze the degradation of mixed reactive azo dyes at a concentration of 100–1000 mg/L. The chemical oxygen demand (COD) removal increased from 34% to 61.15% and then dropped to 21.16% at the highest used concentration. The biochemical oxygen demand (BOD) removal decreased from 63% to 55.55% to 28.14% with an increasing dye concentration. The biosorption experiment and dried activated sludge (DAS) successfully removed about 0.300 mg of dyes by absorption within 2 hours. A toxicity assessment was carried out by employing a phytotoxicity test on Vigna radiata . The percentage of germination was used to detect the toxic effects of untreated dye-containing wastewater on plant growth. The treated wastewater showed 100% germination compared to 70% in untreated wastewater containing 100 mg/L mixed dyes, confirming the treatment's efficacy.